Pelatihan Media Pembelajaran Berbasis E-Learning, Schoology Bagi Guru SMK Program Keahlian Administrasi Perkantoran Di Kabupaten Jombang Jawa Timur: Pelatihan Media Pembelajaran Berbasis E-Learning, Schoology Bagi Guru SMK Program Keahlian Administrasi Perkantoran Di Kabupaten Jombang Jawa Timur - Rosy, Brillian; Ranu, Meylia Elizabeth; Nugraha, Jaka; Handini, Han Tantri (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2018)
Training of learning media based on e-learning schoology held for teachers of MGMP SMK Office Administration Expertise Program in Jombang District. Community Service Activities aims to (1). Providing the delivery of materials to teachers about e-learning learning media, schoology, (2). Provide mentoring to teachers to apply e-learning based learning media, schoology. The training conducted by the team of devotion to the community uses lecture method that is when giving material to the participants, discussion and question and answer, and practice of schoology application by TIM PKM to the participants. The results obtained in this training have benefited MGMP economic teachers in Jombang District. Teachers can recognize interesting learning media based on e-learning that is relevant to the 2013 curriculum. Teacher responses are also very positive with this training. The teachers argue that 81.81% of teachers agree that this training is very important as information variations of learning media, especially e-learning that they need. 87.27% of teachers stated strongly agree that with this training, will increase the awareness and willingness of teachers in applying interactive learning media in schools.